The effects of electrode montages in the auditory brainstem response to level specific CE-chirp - Dzulkarnain, Ahmad Aidil Arafat; Noor Ibrahim, Siti Hajra Mu’minah; Anuar, Nur Farah Aida; Abdullah, Siti Aisyah; Tengku Zam Zam, Tengku Zulaila Hasma; Rahmat, Sarah; Mohd Ruzai, Muhammad Amar (2017)
Purpose of the study: To compare the ABR findings from two different electrode montages (ipsilateral and vertical montages) elicited using a level-specific (LS)-CE-Chirp® in normally-hearing subjects at multiple intensities levels. Methods: Twenty-nine normally-hearing adults (18 females, 11 male) participated. The ABR were acquired using two different stopping criteria, (1) a fixed-signal averaging 4000 sweeps and, (2) a minimum quality indicator of Fmp=3.1 with a minimum of 800 sweeps in both electrode montages. Results: Wave V amplitudes were significantly larger in the LS CE-Chirp® recorded from the vertical montage than the ipsilateral montage and from the LS CE-Chirp® than the click ABRs. Waves I and III amplitudes were significantly larger and consistently identified from the ipsilateral LS CE-Chirp® than from the other montages and stimulus combinations. The differences in the quality of the ABR recording between the vertical and ipsilateral montages were marginal. Conclusions: Overall, the result suggested that the vertical LS CE-Chirp® ABR had a high potential for a threshold-seeking application, because of a higher wave V amplitude. The Ipsilateral LS CE-Chirp® ABR, on the other hand, might also have a high potential for the site of lesion application, because of (i) larger waves I and III amplitudes and (ii) all prominent waves were consistently identified.